Karakteristik Seduhan Daun Pletekan (Ruellia tuberosa L.) dengan Penambahan Variasi Konsentrasi Kayu Manis - Prasetia, Retno; Palupi, Pratiwi Jati (JURNAL AGROTEKNOLOGI, 2023)
Pletekan leaves (Ruellia tuberosa L.) used as antidiabetic (type 2) contains flavonoid (polyphenol compounds) to prevent the formation of oxidative stress because of excess amount of glucose. In the previous research, naturally brewed of pletekan leaves combined with cinnamon gave the best result in taste and gave the highest concentration of tannin and phenol than other natural flavor (bay leaves, ginger, and pandan leaves). Thus, in this research, the variation concentration of cinnamon added in brewed of pletekan leaves that gave the best result was studied. This study was arranged in randomized design with six concentrations of cinnamon and three replications. The parameters analyzed were total phenolic, tannin, antioxidant activity, and organoleptic results (hedonic test) that was analyzed with ANOVA at 5% level. The result showed that the addition of the highest cinnamon concentration (S6) gave the highest concentration of phenol (224.88 ± 1.85 mg/L) and tannin (227.18 ± 1.67 mg/L) with the highest inhibition percentage as antioxidant (55.53 ± 0.16 %). In the organoleptic results, combination of pletekan leaves with the highest cinnamon concentration (S6) gave the highest preferred color (63.39%), taste (61.63%), and odor (70.2%), thus this one was the best combination in giving the preferred taste of beverage. So that, naturally brewed of pletekan leaves combined with cinnamon could increasing taste of it and expected to be a one of beverage from leaves. The brewed of pletekan leaves combined with cinnamon could increasing taste of it and expected to be a one of beverage from leaves as a raw material. Keywords: cinnamon, herbal beverage brewed, pletekan leaves